SEXUAL DIMORPHISM AND GONADAL DEVELOPMENT OF A RARE MURREL SPECIES CHANNA BLEHERI (BLEHER) IN ASSAM - GOGOI, RINKU; S. BEHERA,; BORAH, BIBHA CHETIA; BHUYAN, SONMOINA (The Bioscan, 2013)
The reproductive biology of a rare murrel species Channa bleheri (Bleher) commonly known as ‘rainbow snakehead’ was studied during 2010-2011 in the laboratory of Faculty of Fishery Science, WBUAFS, Kolkota, West Bengal. The study revealed that the sexual dimorphism in C. bleheri exists in the form of a prominent dark blotch in the dorsal fin of the male fish which becomes distinct with the advancement of the maturity stage. Round or oval vent in female and elongated genital in male is another distinctive characteristic for identification of sexes in this species particularly during the breeding season. The Gonado somatic index (GnSI) in male was found to ranges between 0.127- 0.161% while in female it ranges from 0.810 - 3.519%. The peak GnSI value of male was during April to June (0.159-0.161%) while in female the highest value of GnSI were recorded during April to July (2.938- 3.519%). The presence of only one batch of maturing/mature ova indicates that the species breeds only once in a year which is supported by GnSI values exhibiting a single annual peak in both male and female.